Incerteza democrática, legitimidade por reflexividade e jurisdição constitucional: o fundamento (simbólico) do exercício do poder pelo Supremo Tribunal Federal - Brum, Guilherme Valle (Universidade do Vale do Rio dos Sinos, 2018)
This thesis addresses the democratic legitimacy of constitutional jurisdiction. The aim is to defend legitimacy by the exercise of power, the so-called "legitimacy by reflexivity", based on the democratic theory of Pierre Rosanvallon, benefited by the political philosophy of Claude Lefort and the theories of law and democracy by Ronald Dworkin. The intention is that this theoretical arrangement be convincing and adequate to justify the countermajoritarian power of the constitutional courts when performing the judicial review of political acts (laws and public policies) emanating from the Legislative and Executive powers, which have a democratic legitimacy of investiture, conferred by the electoral-majority procedure. One of the main conclusions is that the democratic-reflexive model is adequate to support the authority of the constitutional courts. Furthermore, the thesis concludes that this type of legitimacy does not correspond to a statute, but to a standard, to be measured by the exercise of judicial power. It is a matter of degree, essentially interpretive. Another conclusion of the work is that the integrity of law is part of the symbolic dimension of power and, to that extent, its function is to provide reflexively an identity, at the level of principles, for society. Although it is an identity that is inherently provisional and disputable, considering the open, plural, and future character of democratic regimes.
Keywords: Democracia; Legitimidade por reflexividade; Jurisdição constitucional; Direito como integridade; Democracy; Legitimacy by reflexivity; Judicial review; Law as integrity; ACCNPQ::Ciências Sociais Aplicadas::Direito